1985
DOI: 10.1002/1097-0142(19850515)55:10<2459::aid-cncr2820551025>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nipple and areola in early breast cancer

Abstract: In 141 mastectomy specimens, performed for invasive or noninvasive carcinomas, histopathologic study was performed to assess the extent of nipple‐areola involvement by the tumor. In this study, patients were excluded if (1) the tumor was located beneath the areola; and (2) nipple and/or areola abnormalities were clinically present. Tumor involvement of the nipple and/or areola was found in 44 of 141 specimens (31%), with intraductal growth in 36 (82%) of 44, stromal invasion in 3 (7%), and ductal and stromal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 5 publications
2
50
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] The indications for NSM are clinically decided in consideration of these risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11] The indications for NSM are clinically decided in consideration of these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, centrally located tumors have been regarded as a contraindication of NSM in previous reports, whereas centrally located tumors were considered to be suitable for E-NSM in our study, except in cases with suspicious NAC involvement as assessed by physical examination and MRI. [1][2][3][6][7][8][9][10][11] The two NACs with nipple involvement accounted for 18% (2 of 11) of the breasts with suspicious extensions near the nipple as viewed by MRI. The other NACs without suspicious involvement on MRI examination (85 of 87, 98%) all tested negative for malignancy in the final histology examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The terminal duct lobular unit has been identified as the location for the development of all breast cancer, and a 2008 study identified the presence of terminal duct lobular units in the nipples of 9% of patients (10,11). The rate of occult malignancy detected in the NAC in mastectomy specimens has varied widely with studies reporting an incidence of 1-31% (12)(13)(14)(15)(16). Over the years, a number of prospective and retrospective studies have demonstrated a cancer recurrence rate in the NAC of up to 2%, with local recurrence rates ranging from 1-6% (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Performance of conservative procedure necessitates the knowledge of frequency with which the nipple areola complex is involved in carcinoma of breast 6 Reported rates of neoplastic involvement of NAC by various studies range from 0% to 58% [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . The proportion of breast carcinoma cases associated with nipple discharge ranges from 1.6% to 13%.…”
Section: Discussionmentioning
confidence: 99%